Covid-19 in Rio de Janeiro/Brazil: efforts of hospital pharmacy services - Jullian T. SILVA; Sharon S. LANDGRAF; Isabelly A. SENA; Juliana S. FRANÇA; Vivian A. SILVA (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2021)
Objective: To investigate the efforts of hospital pharmacy services in Brazilian public hospitals during the coronavirus pandemic. Methods: A cross-sectional study about practical and routine hospital pharmacy services in hospitals in the city of Rio de Janeiro (Brazil) was developed. The online survey consisted of 22 questions (3 multiple choice questions, 14 yes/no questions and 5 open-response questions) and the instrument was applied to 20 frontline pharmacists of 6 different hospitals from September 15th to 30th of 2020. Descriptive analysis was made by means of estimation of proportions. Results: We observed that 12 of the 20 participating pharmacists were trained about the new protocols and practice. Two hospitals have altered their Pharmacy Department, creating two groups: (1) services supply of COVID-19 and (2) services supply for others disease or complications. It was found that 3 of the 6 hospitals implemented an exclusively electronic medical prescription system and all of them used individualized dispensing system. At least one pharmacist of each hospital reported a lack or shortage of one or more drugs used in the COVID-19 treatment. Six main causes of drug scarcity were cited and 5 hospitals pointed two of them: increased cost of drug manufacturing and insufficient quantities of raw materials. In addition, we found out that essential ICU drugs, such as ceftriaxone, azithromycin, fentanyl and midazolam were the most prescribed ones, being cited by 5 hospitals (each one). Conclusion: This study showed that pharmaceutical services from six public hospitals of the city of Rio de Janeiro have been adjusted and redesigned to fight the COVID-19. Furthermore, this work can contribute to a more comprehensive vision of the pharmaceutical community about their challenges in the fight against COVID-19 and to provide positive suggestions for improving pharmacy practices.